Evaluation of the Capabilities of Various Local Bamboo as the Places of Milk Fermentation without Inoculant of Lactic Acid Bacteria - Miwada, INS; Lindawati, SA; Hartawan, M; Sutama, INS; Ariana, INT; Tegik, IP (ANIMAL PRODUCTION, 2011)
Abstract. This research was conducted to evaluate the capabilities of the various local bamboos without the inoculation of lactic acid bacteria (LAB) in milk fermentation. The method used in this study was completely randomized design (CRD) with three treatments, namely D (delepung bamboo); A (ampel bamboo) and T (tali bamboo). The results of the study showed that fermentation in tali bamboo produced the lowest pH value (4.82) followed by ampel bamboo (4.87) and delepung bamboo (4.97). Low pH values were followed by a high total acidity with the results respectively 0.82%; 0.80% and 0.78%. Similarly, the highest level of product consistency was in tali bamboo treatment (1.08 min) followed by ampel bamboo (0.53 min) and delepung bamboo (0.38 minutes). Product moisture content was also the lowest in tali bamboo treatment (87.28%) followed by ampel bamboo (87.53%) and delepung bamboo (88.70%). Never the less the capability of tali bamboo as a natural incubator is not significantly different to delay delepung bamboo and ampel bamboo reviewed from protein percentage and fat product. While the total LAB found in the product of tali bamboo treatment (5.82 x 104 CFU/g) was significantly more than delepung bamboo (1.60 x 104 CFU/g) and ampel bamboo (2.37 x 104 CFU/g). The conclusion of research was that the ability of the performance of LAB powder allegedly found in bamboo and its function of milk fermentation was more dominant on tali bambooKey Words: local bamboo, cow milk, fermentation technology, lactic acid bacteriaAnimal Production 13(3):180-184 (2011)